Efektivitas Model Pembelajaran Aktif Dengan Metode Question Student Have (QSH) Terhadap Keaktifan Belajar PAI Peserta Didik Di SMK Negeri 7 Bandar Lampung - Nalita Azzura; Heru Juabdin Sada; Erni Yunita; Saiful Anwar; Syamsuri Ali (Educatio, 2025)
This study aims to examine the effectiveness of the active learning model using the Question Student Have (QSH) method in enhancing students’ learning activeness in Islamic Religious Education (PAI) subjects at SMK Negeri 7 Bandar Lampung. The research background was based on the low indicators of learning activeness, particularly students’ courage to ask questions. The method employed was a quasi-experimental design with a posttest-only control group design, involving two Grade XI classes as the sample: the experimental class, which received QSH treatment, and the control class, which was taught through conventional instruction. The research instrument was a learning activeness questionnaire that had been tested for validity and reliability, and the data were analyzed using a t-test. The findings revealed that the implementation of QSH had a significant effect on improving students’ learning activeness, especially in terms of their willingness to participate and engage in discussions. The anonymous mechanism in formulating questions proved effective in reducing shyness and fear of making mistakes, thereby fostering more optimal participation. The novelty of this study lies in the application of QSH within the vocational education context, which not only enhances activeness but also develops students’ soft skills, such as critical thinking, communication, and collaboration, all of which are highly relevant to the demands of the workplace. The implications of this study contribute to the development of more interactive, enjoyable, and meaningful PAI learning strategies at vocational schools. Furthermore, these findings broaden the scope of QSH effectiveness, which has previously been widely applied at the elementary and general secondary levels, to also be relevant in vocational education